Grooming Risk Factors in Adolescents with Abuse Histories: Insights from Chilean Reparative Programs - Pamela Melo Laclote; Jonathan Martínez-Líbano; Cristian Céspedes; Sergio Fuentealba-Urra; Nicolás Santander Ramírez; Roberto Iturra Lara; María-Mercedes Yeomans-Cabrera (Adolescents)
The increasing use of digital platforms by adolescents has brought to light critical vulnerabilities related to online grooming. This study explores the risk factors associated with grooming among adolescents aged 12 to 17 years enrolled in a Reparative Program for Abuse in Chile. Using a non-experimental, quantitative, exploratory cross-sectional design, a sample of 50 adolescents was evaluated. Data collection employed validated instruments, including the Okasha Scale for Suicidality (EOS), the Depression Anxiety Stress Scale-21 (DASS-21), the Subjective Well-being Scale (EBS-8), and the Online Grooming Risk Scale (OGR-S). Findings revealed significant associations between grooming and variables such as excessive cellphone use, number of virtual social networks, lack of social connections, economic hardships, and depressive symptoms. Regression analysis highlighted that adolescents with unrestricted internet access, poor social interaction skills in face-to-face contexts, and exposure to environmental risk factors exhibit a heightened likelihood of experiencing grooming. These results underscore the necessity for targeted preventive interventions and policy enhancements to safeguard adolescents in vulnerable circumstances.